2001
DOI: 10.1007/s004150170264
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord compression due to extramedullary haematopoiesis in two patients with thalassaemia: complete regression with blood transfusion therapy

Abstract: Extramedullary haematopoiesis, a common finding in thalassaemia, is rarely localized in the spinal cord and even more rarely has neurological manifestations. We present two patients suffering from thalassaemia (intermedia and beta homozygous) and paraparesis due to spinal cord compression from intrathoracic extramedullary haematopoietic masses. Diagnosis was based on magnetic resonance imaging findings, and treatment consisted of blood hypertransfusions. The majority of published cases have been successfully t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 12 publications
(27 reference statements)
0
24
0
2
Order By: Relevance
“…However, the resolution was too rapid to be attributable to steroids alone. It has been shown that hyper-transfusion therapy helps to shrink extra-medullary hematopoietic tumors and alleviate the compressive effect on spinal cord [3,5,6,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the resolution was too rapid to be attributable to steroids alone. It has been shown that hyper-transfusion therapy helps to shrink extra-medullary hematopoietic tumors and alleviate the compressive effect on spinal cord [3,5,6,9].…”
Section: Discussionmentioning
confidence: 99%
“…The resultant anemia, hemolysis and ineffective erythropoiesis form the fundamental pathology for clinical manifestations of beta-thalassemia. In extreme cases of dyserythropoiesis, extra-medullary hematopoietic tumors may develop [3][4][5][6]. Acute neurological complications in patients with beta-thalassemia have been reported in association with cerebral ischemia, spinal cord fractures and compression from extra-medullary hematopoietic tumors [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The management of spinal cord compression remains controversial. Radiotherapy with blood transfusions [12], hypertransfusion with hydroxyurea therapy [13,14], or only blood transfusions [11,15] were found to be successful in the complete regression of haematopoietic masses. The different treatment strategies for symptomatic pleural effusion and haemothorax at intrathoracic EMH include pleurocentesis [9], tube thoracostomy [1], pleurodesis with tetracycline [16], and low-dose radiation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Noninvasive studies, including chest roentgenograms, CT and magnetic resonance imaging, can establish the EMH in most cases [10,11,18]. Bone marrow scanning with TC-99M sulfur colloid is a convenient noninvasive method of further establishing the diagnosis [2,8,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation